2022
DOI: 10.1088/1755-1315/990/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

Increase in environmental safety of recovery boiler

Abstract: To improve environmental safety of a recovery boiler (RB) it is suggested to use a monitoring and diagnostic system that allows detecting faults of the normal process mode at early stages and preventing their development in emergency situations. The RB diagnostic model structure was developed and faults and possible abnormal situations in RB were analyzed qualitatively with the use of HAZOP methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Inside the washing chamber, from above, to the transverse beams (pos.12), a beam No. 12 of an I-section (pos.11) is fixed, along which a cart with a frame attached to it (pos.13), made of a steel pipe with a diameter of 50 mm, moves along the chamber on rollers (pos.13) [11]. with holes 4 mm in diameter in a checkerboard pattern, the distance between the holes in a row is 50 mm.…”
Section: Resultsmentioning
confidence: 99%
“…Inside the washing chamber, from above, to the transverse beams (pos.12), a beam No. 12 of an I-section (pos.11) is fixed, along which a cart with a frame attached to it (pos.13), made of a steel pipe with a diameter of 50 mm, moves along the chamber on rollers (pos.13) [11]. with holes 4 mm in diameter in a checkerboard pattern, the distance between the holes in a row is 50 mm.…”
Section: Resultsmentioning
confidence: 99%
“…It makes it possible to construct a temperature dependence not from one single measurement location, but from all areas of the research object. Similar works were considered in [92][93][94][95][96][97][98][99][100][101][102][103][104][105][106] but were applied to other objects. Thus, the logicality of the chosen research path was confirmed.…”
Section: The State Of Knowledge Of the Problemmentioning
confidence: 99%
“…determination of permissible technologically safe modes during the exploitation of MW deposits (formation of target functions for well network control systems) [20,21]; • determination of the optimal number of production wells; • calculation of parameters of distributed controllers for local control systems [1,22,23];…”
mentioning
confidence: 99%